Dług publiczny w ujęciu ekonomicznym i prawnym. Zmienność długu publicznego w wybranych gospodarkach pozaeuropejskich po 2007 na tle państw Unii Europejskiej - Malinowski, Dariusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The two main aims of the text were comparative analysis of several legal methodologies for defining public debt developed by international organizations and presenting the Polish legal methodology of calculating public debt while pointing out to the differences between methodologies. Presentation of the concept of the budget deficit and public debt in economic theory served as introduction to the description of legal approach to public debt. The second part of the study examines the economic volatility of the state budget deficit and public debt in selected non-European economies after 2007. The analysis was carried out on a group of sixty-largest economies in the world by GDP at market prices by purchasing power parity. The state of public finance of non – European economies is shown in comparison with the state of EU public finance